Updates on acute diverticulitis: Epidemiological, pathophysiological and clinical aspects (Research, Society and Development, 2024)
Introduction: Acute diverticulitis is a prevalent condition that arises from the formation of diverticula in the intestinal colon, and their presence can be asymptomatic or symptomatic, and may or may not become inflamed throughout life. Therefore, the objective of this work is to discuss and present the most recent information about acute diverticulitis. Methodology: This is an integrative review about acute diverticulitis and its related aspects. Data from the Virtual Health Library (VHL), Scientific Electronic Library of Medicine (SciELO) and National Library of Medicine (PubMed) databases were used, by crossing the descriptors “diverticulitis”, “abdominal pain”, “epidemiology” and “physiology” to answer the question formulated through the PICO strategy. Results and Discussion: It is estimated that more than 50% and more than 60% of people aged 60 and 80, respectively, have diverticula in the colon, however, despite the relationship with age, young people have an increasing prevalence of acute diverticulitis. The mechanism behind the formation of diverticula is not specifically known and treatment is not yet standardized, with one of the main discussions being the use of antibiotics in uncomplicated acute diverticulitis. It is known that the clinical presentation of the uncomplicated acute form includes left abdominal pain, fever and malaise, leukocytosis may appear and, in case of complications, patients may develop perforation, peritonitis and other conditions. Conclusion: In view of the above, it is necessary to make people aware of the risk factors, as well as to produce larger studies so that a treatment can be defined and better standardized.